2015
DOI: 10.1158/0008-5472.can-14-2798
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of EphA2 Converts It from a Tumor Suppressor to an Oncoprotein

Abstract: Eph receptor tyrosine kinases are considered candidate therapeutic targets in cancer, but they can exert opposing effects on cell growth. In presence of its ligands, Eph receptor EphA2 suppresses signaling by other growth factor receptors, including ErbB, whereas ligand-independent activation of EphA2 augments ErbB signaling. To deploy EphA2-targeting drugs effectively in tumors, the anti-oncogenic ligand-dependent activation state of EphA2 must be discriminated from its oncogenic ligand-independent state. Sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 43 publications
0
69
0
Order By: Relevance
“…Overexpressed EPHA2 can be phosphorylated at S897 by activated AKT and can function in a ligand-independent manner to promote cell growth, xenograft tumor development, anoikos resistance (42), and migration of tumor cells (43)(44)(45)(46). Additionally, overexpressed EPHA2 is cleaved at the membrane by MT1-MMP metalloprotease and switches its function from ligand-dependent tumor suppressor to ligand-independent tumorpromoting factor (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed EPHA2 can be phosphorylated at S897 by activated AKT and can function in a ligand-independent manner to promote cell growth, xenograft tumor development, anoikos resistance (42), and migration of tumor cells (43)(44)(45)(46). Additionally, overexpressed EPHA2 is cleaved at the membrane by MT1-MMP metalloprotease and switches its function from ligand-dependent tumor suppressor to ligand-independent tumorpromoting factor (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…47,48) Although Sugiyama et al 47) showed that the cleavage site was Y 385 -I and T 395 -I and Koshikawa et al 48) found that it was S-427 F and S-432 V, cleaved EphA2 had a ligand-insensitive form to promote cancer migration. Therefore, EphA2 cooperates with MT1-MMP to play a role as a tumor initiator.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%
“…In addition, cleaved EphA2 processed by MT1-MMP also activates the Ras-ERK and PI3K-Akt pathways, even when ephrin-A1 is overexpressed. 47,48) Notably, Koshikawa et al, reported that phosphoSer-897 EphA2 and MT1-MMP were co-localized in ovarian carcinoma, but not in the normal ovary. 48) In addition, cleaved EphA2 was required for tumor growth and metastasis of A431 cells in vivo.…”
Section: Cell Motility and Cell Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that membrane type-1 matrix metalloproteinase (MT1-MMP) on tumor cells cleaves EPHA2 at the extracellular domain and the resultant truncated and membrane-anchoring forms of EPHA2 promote oncogenic signaling [33]. These findings suggest that tumor cells contain truncated forms of EPHA2 on their cell surface which are important for EPHA2-targeting cancer therapy using monoclonal antibodies (mAbs) that mediate antibody-dependent cellular cytotoxicity (ADCC) [25].…”
Section: Discussionmentioning
confidence: 99%